High-density EMG Reveals Novel Evidence of Altered Masseter Muscle Activity During Symmetrical and Asymmetrical Bilateral Jaw Clenching Tasks in People With Chronic Nonspecific Neck Pain. Issue 2 (February 2017) - Testa, Marco; Geri, Tommaso; Gizzi, Leonardo; Falla, Deborah
Abstract : Objectives: To characterize the distribution of masseter muscle activity and force control during bilateral jaw clenching tasks in people with chronic nonspecific neck pain, without an associated temporomandibular disorder. Methods: Twelve volunteers with nonspecific neck pain and 12 age-matched and sex-matched healthy individuals participated. Submaximal symmetrical and asymmetrical bilateral jaw clenching was performed with and without visual feedback of force. Force performance was assessed with indices of accuracy (mean distance, offset error) and precision (standard deviation, coefficient of variation of force). High-density, 2-dimensional, surface electromyography (EMG) was recorded to characterize bilateral masseter muscle activity. The EMG root mean square was computed for each location of the electrode grid to form a map of the EMG amplitude distribution, and the location of the center of activity was measured. Results: The patient group showed a different distribution of masseter muscle activity compared with pain-free individuals during both symmetrical and asymmetrical bilateral jaw clenching. The position of the center of activity was positioned more cranial ( P <0.001; right masseter only) and more anteriorly in the patient group ( P <0.0001). In addition, the patients with chronic neck pain displayed higher levels of masseter muscle activation compared with the control participants regardless of the specific task performed ( P <0.0001). Discussion: People with chronic neck pain display increased activation and altered distribution of masseter muscle activity during a jaw-clenching coordination task. These results provide a greater appreciation of how secondary orofacial pain or temporomandibular disorders may develop in people with neck pain.